Perspectives and Socioeconomic Influences of Personal Protective Equipment Waste Management on Post-COVID-19 - Suhardono, Sapta; Septiariva, Iva Yenis; Mulyana, Rachmat; Suryawan, I Wayan Koko; Ulhasanah, Nova; Prayogo, Wisnu; Sari, Mega Mutiara (Jurnal Kesehatan Masyarakat, 2024)
The COVID-19 pandemic brought an upsurge in Personal Protective Equipment (PPE) usage, leading to emergent challenges in its post-use management, especially in urban centers like Jakarta. This study conducted a quantitative exploration, employing simple random sampling techniques, to investigate Jakarta citizens; perceptions of PPE waste management. Two significant factors, "Safe Management and Regulation" and "PPE Waste Handling," were identified as paramount in addressing the issue. Through cluster analysis, the population was segmented into three distinct clusters: "Regulatory-Driven Safety Respondents," "Operational PPE Focus Respondents," and "Minimal Management Respondents." The study also unveiled a notable influence of socioeconomic variables on PPE waste management attitudes, particularly occupancy and income. These findings give policymakers, urban planners, and researchers invaluable insights, emphasizing the need for a dual-focused approach encompassing regulatory and operational strategies tailored to specific demographic segments for optimal impact.